Thracians in the Attalid Army - Sekunda, Nicholas Victor (Anabasis. Studia Classica et Orientalia, 2020)
This article attempts to reconstruct the pattern of employment of Thracian mercenaries in Attalid service. It seems that a Thracian group called the Tralles were particularly in favour. These people specialised in fighting as hamippoi: light-infantry trained to fight in combination with the cavalry. They are mentioned in OGIS 266, an inscription that can be dated to 263 BC, reconciling Attalid troops who had mutinied with their ruler. Tralles are also mentioned in Attalid service at the battles of Magnesia (190 BC) and Olympos (189 BC). Thracians are also mentioned fighting in Attalid service at the latter battle, but this is the only reference to Thracians other than Tralles serving in the Attalid army before the Revolt of Aristonikos. Thracian names are also attested epigraphically at Aigina, probably serving in the garrison the garrison which the Attalids maintained on the island from 210 BC until the fall of the kingdom in 133 BC. These names could be borne by either Trales or ‘other’ Thracians. Apart from this, Thracians are absent from the 4 preserved inscriptions listing mercenaries in Attalid service. This neither gives the impression of the Attalid monarchs recruiting Thracian mercenaries in great numbers, nor of settlement of Thracian former mercenaries in military colonies in Attalid territory. Valerius Maximus mentions that Aristonikos had ‘a large number’ of Thracians in his army. These could have been specially recruited for the revolt, rather than soldiers formerly employed in the Attalid army. The majority of Thracian names attested within the borders of the former Attalid kingdom are not traces of settlement of Thracian mercenaries formerly in Attalid service, but of males using mixed family naming systems formerly in Macedonian service who fled Macedonia after the fall of the kingdom in 168 BC.